Análisis del mercado del turismo emisivo y su relación entre las agencias de viajes mayoristas e internacionales en la ciudad de Guayaquil - Carvache Franco, Wilmer (2010)
This research stems from the need to document how to market tourism emissive in Guayaquil and present the entities involved and functions. These unions are the main sources of employment for tourism professionals, for this reason we uphold the importance, preventing the disintegration of the tourism chain consisting of customer, wholesale travel agent, travel agency international international operator. Deficiencies are present in the emissive tourism sector in organization and involvement of regulators causing dissent, rivalry and economic damage